2008
DOI: 10.1007/s10404-008-0292-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of inlet design on mass transfer in gas–liquid rectangular microchannels

Abstract: The length of the gas bubbles as well as of the liquid slugs in Taylor flow in rectangular microchannels was studied. At constant flow ratios of the gas and the liquid phase, we were able to vary the unit cell length, and therefore the gas bubble length as well as the liquid slug length by factor 4 solely by changing the inlet geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 15 publications
2
35
1
Order By: Relevance
“…44,45 In general, increasing the gas velocity at a constant liquid velocity leads to shorter liquid slugs, and our experimental results demonstrated this principle, as shown in Figure 8a. Moreover, some researchers [46][47][48] had proposed empirical correlations for predicting the length of liquid slug of Taylor flow in microchannels due to its importance. In these correlations, the liquid slug length was correlated by considering Reynolds number, capillary number and gas holdup, and the Reynolds number was most emphasized.…”
Section: Effect Of Superficial Gas Velocity On Hydrodynamics and Liqumentioning
confidence: 99%
“…44,45 In general, increasing the gas velocity at a constant liquid velocity leads to shorter liquid slugs, and our experimental results demonstrated this principle, as shown in Figure 8a. Moreover, some researchers [46][47][48] had proposed empirical correlations for predicting the length of liquid slug of Taylor flow in microchannels due to its importance. In these correlations, the liquid slug length was correlated by considering Reynolds number, capillary number and gas holdup, and the Reynolds number was most emphasized.…”
Section: Effect Of Superficial Gas Velocity On Hydrodynamics and Liqumentioning
confidence: 99%
“…Generally, the models performed well with respect to their own data set, but poorly against external data sets. The major issue is that many of the models treat α and β as fitting parameters in the development of empirical correlations for the specific T-junction design under study [8,11,[16][17][18][19][20]. These correlations take the general form of…”
Section: Introductionmentioning
confidence: 99%
“…At increased continuous phase flow rate, the droplets become smaller due to increased shear on the emerging droplets (Fries & Rudolf von Rohr 2009;Yeom & Lee 2011a). When the capillary number and the flow rate ratio are kept constant, the normalised droplet size is dependent on the geometry and increases with decreasing continuous phase channel width (Fries & Rudolf von Rohr 2009;Garstecki et al 2006;Gupta & Kumar 2010a;Wehking et al 2013).…”
Section: Channel Dimensionsmentioning
confidence: 98%
“…Droplets and bubbles formed in the squeezing or dripping regime decrease in size with decreasing the dispersed phase channel width (Christopher et al 2008;Fries & Rudolf von Rohr 2009;Yeom & Lee 2011a), further it was found that the effect of the dispersed phase channel width on droplet volume is larger at low capillary number (Christopher et al 2008). For the critical capillary numbers related to transitions between regimes; increasing the aspect ratio decreases Ca c for transition from dripping to jetting and to parallel flow (Chen et al 2012;Garstecki et al 2006), whereas the transition from squeezing to dripping is hardly affected (Wehking et al 2013).…”
Section: Channel Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation